Biotrophic interaction of Sporisorium scitamineum on a new host—Saccharum spontaneum. (February 2016) - Jose, Robinson C.; Louis, Bengyella; Goyari, Sailendra; Waikhom, Sayanika D.; Handique, Pratap J.; Talukdar, Narayan C.
Highlights: First microscopic examination of biotrophic interaction of Sporisorium scitamineum on a new host —Saccharum spontaneum . Fungus S. scitamineum colonizes S. spontaneum non-systemically to form smut gall. Infection of S. spontaneum by S. scitamineum thwarts inflorescence Infection of S. spontaneum leads to confined development of smut gall and causes structural reorganization of internal tissues. Abstract: Sporisorium scitamineum is a biotrophic smut fungus harbored inside the smut gall on the top internodal region of Saccharum spontaneum, a wild relative of sugarcane ( Saccharum officinarum ). The interactions of spined conidia of S. scitamineum with S. spontaneum were examined during the different stages of plant growth starting from the bud stage to the decaying stage. The spores in the soil from the polyetic inocula grew into confined epidermal cells of the buds and finally sporulated in the topmost internodal region. Hyphae invasion of the plant tissues were restricted to the point of infection. Culms of infected plants in late October sporulated, notably; hyphal sporulation produced shorter hyphal stolons. Remarkably, the nodal regions of infected plants had no spores and fragmented hyphae. On the basis of microscopic analyses, hyphae and spores were absent in all internodes above the ground till the topmost smut gall region. This result indicated that, S. scitamineum undergoes tissue-confined invasion of S. spontaneum . By associating culture medium method with polymerase chain reaction (PCR) on plant portions void of smut gall, S. scitamineum was not detected, indicating that colonization was not systemic. It was observed that the biotrophic interaction resulted in structural reorganization in the restricted region of infection forming erect cylindrical structure, in which the fungus was sandwiched between the central stalk and sheath, and possibly played a key role in preventing inflorescence. Comparatively, a significant difference in the rate of teliospores germination between reference Ustilago esculenta (26.6%, P < 0.05) and S. scitamineum (62.9%, P < 0.05) at 20° C was observed. This study also provides insights on the effect of different temperature regimes on the germination of S. scitamineum teliospores in vitro .